Importance of LCMS in Forced Degradation Studies for new Chemical Entities: Life Sciences-Biochemistry for Better Diagnosis and Therapy - Anusha Kota; M.V.Kumudha Valli (International Journal of Life Science and Pharma Research, 2022)
Forced degradation studies shows the chemical behaviour of the molecule which in turn helps in the development of formulation and package. In addition, the regulatory guidance is very general and does not explain about the performance of forced degradation studies. In pharmaceutical industry, mandatory degradation tests are important to determine the mechanisms and measure the potential degradants during the analysis of drug material and to help to elucidate the composition of degradation materials. The Liquid Chromatography/ Mass Spectrum analysis (L.C.M.S) is a short term widely established liquid chromatography and a methodology utilizing a natural fluid process. L.C.M.S. is commonly employed in the laboratories for qualitative testing of drug substances, drugs and biological samples. Degradation studies, metabolic screening, metabolite identity and in vivo drug screening, impurity identification, amide mapping, glycoprotein mapping were consistently used in pharmaceutical development by LCMS. The FDA and ICH guidelines sets out the requirement for stability testing data to understand how the quality of the drug substance and drug product changes over time under the influence of various environmental factors. Knowledge of molecular stability helps to select the correct formulation and package as well as to provide proper storage conditions and shelf life, which is essential for regulatory documentation. Active pharmaceutical ingredients (APIs) may form impurities when exposed to excipients or environmental variables such as light, high temperatures, acidic or basic conditions, humidity; and the oxidative atmosphere. Considering that these impurities may have an impact on safety and efficacy, it is necessary to know how these impurities are produced from the drug product and to establish the path of their formation. In this context, forced drug degradation studies have been used to characterize the physicochemical stability of APIs. These studies are also essential in the validation of analytical methodologies, in order to demonstrate the selectivity of methodologies. The API and its impurities and to develop strategies to avoid the formation of degradation products. The objective of this review is to demonstrate how forced degradation studies have been conducted and application of LCMS tools in related studies.